PENGGUNAAN TEKNOLOGI INFORMASI DI DUNIA BISNIS DAN PERBANKAN - Amin Wahyudi . (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2009)
ABSTRACT The new millennium heralds the emergence of a powerful new imperative for conducting business activity and banking activity that has global implication for marketers and the marketing discipline. Now, transaction are made direct and on-line trough a wide variaty of information technology and electronic platforms such the internet and world wide web (www), electronic data inter-change, fax, e-mail, ATM and smart card to facilitate payment and obtain instant cash Keywords: information technology, business, banking, transaction